Aligning Adolescents to the Public Sphere: The Teen Serial Skam and Democratic Aesthetic - Skarsbø, Synnøve; Dahl, John Magnus (Javnost-The Public, 2019)
The Norwegian online teen serial Skam, produced by public broadcaster NRK, makes up an interesting case for exploring the role of popular culture within the public sphere. Since first premiered in 2015, Skam has become an international phenomenon, engaging and connecting teenagers all over the world in online discussions mainly concerning the serial’s characters and romantic plots. Through empirically based reception studies and analysis of online fan activity, we find that these discussions have civic potential and may “build” teen audiences as citizens. Furthermore, we argue that the genre-specific and aesthetic characteristics of Skam facilitate for this to happen. Melodrama, as well as the liveness created by the publication method, are the main features of the serial’s democratic aesthetic.